Building effective engagement for implementation with i-PARIHS: a collaborative enquiry into paediatric pain care in the emergency department - Suzanne Williams; Samantha Keogh; David Herd; Sharonn Riggall; Roselyn Glass; Clint Douglas (BMC, 2022)
Abstract Background Pain is a central and distressing experience for children in the emergency department (ED). Despite the harmful effects of pain, ED care often falls short of providing timely and effective pain relief. Knowledge translation research targeting systems of care holds potential to transform paediatric pain care. This article reports on the first stages of an implementation project aimed at embedding effective and sustainable practice change in an Australian children's hospital ED. Methods The integrated Promoting Action on Research Implementation in Health Services (i-PARIHS) framework underpinned a cooperative process of engagement to establish a practitioner-led, interprofessional research collaborative. The Kids Pain Collaborative (KPC) aimed to co-design innovation in paediatric ED pain care, facilitating an extensive reconnaissance of research evidence, clinician and family experiences, and local evaluation data. This critical appraisal of the context and culture of pain management generated foci for innovation and facilitation of implementation action cycles. Results Engaging in a complex process of facilitated critical reflection, the KPC unpacked deeply embedded assumptions and organisational practices for pain care that worked against what they wanted to achieve as a team. A culture of rules-based pain management and command and control leadership produced self-defeating practices and ultimately breakdowns in pain care. By raising a critical awareness of context, and building consensus on the evidence for change, the KPC has established a whole of ED shared vision for prioritising pain care. Conclusions In-depth key stakeholder collaboration and appraisal of context is the first step in innovation of practice change. The KPC provided a space for collaborative enquiry where ED clinicians and researchers could develop context-specific innovation and implementation strategy. We provide an example of the prospective application of i-PARIHS in transforming ED pain care, using a collaborative and participatory approach that has successfully enabled high levels of departmental engagement, motivation and ownership of KPC implementation as the facilitation journey unfolds.